MAKNA FILOSOFIS KEMBAR MAYANG DALAM KEHIDUPAN MASYARAKAT JAWA - Sri Widayanti (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2008)
AbstractKembar Mayang is one of the elements in a Javanesetraditional ceremony. The terminology of Kembar Mayang isknown in a form of janur (young coconut leaf) which is decorated with flowers and leaves in such manner on a banana bar. Kembar Mayang as a typical Javanese flowers arrangement can be seen on an engraving relief which is located on Prambanan temple and named as Kalpataru. The eldest form of Kembar Mayang can be found in Keraton Yogyakarta (Yogyakarta Palace) which is made by the year 1906 in the era of Sri Sultan Hamengku Buwono VII (King of Yogyakarta Palace). There has been many changes of Kembar Mayang style since the year 1950. In Javanese society Kembar Mayang has a philosophical meaning which expresses relation between human being and environment/ nature. Human being and nature/ environment have a cosmological bond. While the Kembar Mayang form shows the existence of aesthetic values,in fact, it is a medium of both human and his/ her ancestors to have a mutual relationship, especially for a king. Kembar Mayang functions as a witness of an event and a guardian. Symbolically Kembar Mayang is a witness of status change from a bachelor/virgin (single) to marital status. Kembar Mayang also can be used as a death witness. Therefore, there are two terms of Gagar Mayang for a witness of bachelor/ virgin passing away, and Kembar Mayang for a witness in marriage ceremony as a ceremonial medium.Keywords: Kembar Mayang, Gagar Mayang, Traditional ceremony, Aesthetic